A randomised controlled trial of fluoxetine versus naltrexone in compulsive sexual behaviour disorder: presentation of the study protocol - Jussi Jokinen; Josephine Savard; Katarina Görts Öberg; Cecilia Dhejne (BMJ Open)
Background Compulsive sexual behaviour disorder is a new disorder in the International Classification of Diseases (ICD-11), and is associated with negative consequences in different areas of life. Evidence for pharmacological treatment of compulsive sexual behaviour disorder is weak and treatment options are limited. This proposed study will be the largest and the first randomised controlled trial comparing the efficacy and tolerability of two active drugs in compulsive sexual behaviour disorder.Methods and analysis Eighty adult participants with compulsive sexual behaviour disorder according to ICD-11 will be randomised to receive either naltrexone 25–50 mg or fluoxetine 20–40 mg for 8 weeks, followed by 6 weeks without treatment. The study will be conducted in a subspecialised outpatient sexual medicine unit at Karolinska University Hospital, Stockholm, Sweden. The study is financed by grants and entirely independent of the manufacturers.Exclusion criteria include severe psychiatric or psychical illness, changes to concurrent medication and non-compatible factors contraindicating the use of either drug. The primary outcome measure is the Hypersexual Disorder: Current Assessment Scale (HD: CAS), and tolerability will be assessed by the Udvalg for Kliniske Undersogelser side effect rating scale (UKU), drug accountability, adherence to treatment and drop-out rate. Participants will complete questionnaires at regular intervals, with the main endpoint for efficacy after 8 weeks (end of treatment) and after 14 weeks (follow-up). Blood chemistry will be repeatedly collected as a safety precaution and for research purposes. The results will be analysed using an appropriate analysis of variance model or a mixed model, depending on the distribution of HD: CAS and the extent of missing data.Ethics and dissemination The Swedish Ethical Review Authority and the Swedish Medical Products Agency have approved the study on 27 May 2020 and 4 June 2020, respectively (ref. no. 2020-02069 and ref. no. 5.1-2020-48282). Findings will be published in peer-reviewed journals and presented at relevant conferences.Trial registration number 2019-004255-36